2017
DOI: 10.5301/jsrd.5000249
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of systemic sclerosis: recent insights of molecular and cellular mechanisms and therapeutic opportunities

Abstract: that results in irreversible scarring and organ failure. In other word, fibrosis is the end-result of a cascade of vascular and immune responses to environmental injury, and represents a failed tissue repair process. There have been advances in understanding of pathogenic processes that reflect the interplay between immune-inflammatory processes and vasculopathy and fibrosis. This review focuses on recent insights of functional consequences of SSc, highlighting three major characteristics of SSc; microvasculop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
251
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 274 publications
(265 citation statements)
references
References 159 publications
1
251
0
1
Order By: Relevance
“…17 Ang II together with endothelin-1 are supposed to promote endothelial mesenchymal transition, therefore promoting systemic fibrosing. 7 Subcutaneous infusion of Ang II was shown by Stawski et al 18 the main target receptor for Ang II, had been previously identified in patients with SSc and linked to increased prevalence of both vascular and fibrotic complications with the higher risk of SSc-related mortality. 7 The significantly elevated serum level of Ang II was found by Kawaguchi et al 4 A discovery of Ang-(1-7) in 1991 revealed a counterbalancing axis in the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…17 Ang II together with endothelin-1 are supposed to promote endothelial mesenchymal transition, therefore promoting systemic fibrosing. 7 Subcutaneous infusion of Ang II was shown by Stawski et al 18 the main target receptor for Ang II, had been previously identified in patients with SSc and linked to increased prevalence of both vascular and fibrotic complications with the higher risk of SSc-related mortality. 7 The significantly elevated serum level of Ang II was found by Kawaguchi et al 4 A discovery of Ang-(1-7) in 1991 revealed a counterbalancing axis in the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…7 Subcutaneous infusion of Ang II was shown by Stawski et al 18 the main target receptor for Ang II, had been previously identified in patients with SSc and linked to increased prevalence of both vascular and fibrotic complications with the higher risk of SSc-related mortality. 7 The significantly elevated serum level of Ang II was found by Kawaguchi et al 4 A discovery of Ang-(1-7) in 1991 revealed a counterbalancing axis in the renin-angiotensin system. This novel angiotensin was produced directly by degradation of Ang II or indirectly from Ang I, and it manifested itself with a wide spectrum of beneficial effects in CVS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations